Memahami Istilah Kerajaan Allah dalam Ajaran Yesus Menurut Injil Markus - Tupa Pebrianti Lumbantoruan; Selviana Putri Naibaho; Agustinus Gulo; Yesica Elisabet Tanjung; Juita Manullang (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses the concept of the Kingdom of God in Jesus' teaching according to the Gospel of Mark. The Kingdom of God is understood as a spiritual and eschatological reality that is present through the ministry of Jesus Christ. In the Gospel of Mark, Jesus' teaching about the Kingdom of God challenges the traditional view that expects the coming of the Messiah as a political leader. Using a qualitative approach, this study examines the verses of Mark 1:15, 4:11-12, 4:30-32, and 10:15 to explain the characteristics of the Kingdom of God, such as its theocentric, messianic, and dynamic nature. The study highlights that the Kingdom of God is the active rule of God in human history, with two main dimensions: